Dampak Minyak Dunia, Energi Terbarukan, dan Kebijakan Moneter Terhadap Laju Pertumbuhan Ekonomi di Indonesia Tahun 1987-2019 - Andi Nur Fauziyah Syafriany; Ika Yuni Wulansari (Seminar Nasional Official Statistics, 2021)
One of the indicators that can determine the progress of a country is economic growth rate. Indonesia as one of developing country has a volatile economic growth rate from year to year. This thing can be affect by some factors in some aspects of life such energy, production factors, and monetary. Therefore, the goal of this study is know the general description of Indonesia’s economic growth rate 1987-2019 and the factors that can affect Indonesia’s economic growth rate, both in the long and short term. This study use Error Correction Mechanism method. The result of this study is world oil production, exchange rate of Rupiah to United Stated Dollar, and interest rate significantly influenced Indonesia economic growth rate in long term. Besides that, gross fixed capital formation, exchange rate of Rupiah to United Stated Dollar, interest rate, and Error Correction Term (ECT) significantly influenced Indonesia economic growth in short term.